2020
DOI: 10.1016/j.celrep.2019.12.017
|View full text |Cite
|
Sign up to set email alerts
|

TRIM32/USP11 Balances ARID1A Stability and the Oncogenic/Tumor-Suppressive Status of Squamous Cell Carcinoma

Abstract: Highlights d ARID1A stability is controlled by the ubiquitin-proteasome system d TRIM32 promotes squamous cell carcinoma progression by degrading ARID1A d USP11 prevents squamous cell carcinoma progression by stabilizing ARID1A d ARID1A loss activates SDC2 to drive squamous cell carcinoma development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Nevertheless, SCCs are characterized by low ARID1A protein expression, indicating that the TRIM32-dependent degradation of ARID1A may represent a relevant mechanism contributing to underexpress this epigenetic factor in SCC. Notably, TRIM32 action is counteracted by the DUB USP11, which promotes the stabilization of ARID1A protein [57]. Consistently, SCC samples show a negative correlation between TRIM32 and ARID1A expression and a positive correlation between USP11 and ARID1A expression.…”
Section: Additional E3s Involved In Sccsmentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, SCCs are characterized by low ARID1A protein expression, indicating that the TRIM32-dependent degradation of ARID1A may represent a relevant mechanism contributing to underexpress this epigenetic factor in SCC. Notably, TRIM32 action is counteracted by the DUB USP11, which promotes the stabilization of ARID1A protein [57]. Consistently, SCC samples show a negative correlation between TRIM32 and ARID1A expression and a positive correlation between USP11 and ARID1A expression.…”
Section: Additional E3s Involved In Sccsmentioning
confidence: 65%
“…Human HNSCC samples also display an elevated level of TRIM32 [54]. Although different TRIM32 substrates underlying its pro-oncogenic function have been identified, a recent report uncovered a novel oncogenic route exploited by TRIM32 in SCCs [57]. Luo et al reported that TRIM32 is able to target the SWI/SNF complex subunit ARID1A, a potential tumor suppressor.…”
Section: Additional E3s Involved In Sccsmentioning
confidence: 99%
“…Based on our observation that SPRTN and USP11 interact (Figure 1 and 2) and because USP11 is a deubiquitinase (Luo et al, 2020, Deng et al, 2018, Orthwein et al, 2015, we investigated whether SPRTN is a substrate for USP11 deubiquitinase. Indeed, we found that overexpression of Myc-USP11 FL, but not C318S catalytic inactive mutant was able to deubiquitinate SFB-SPRTN in HEK 293T cells ( Figure 3A).…”
Section: Usp11 Deubiquitinates Sprtn In Cells and In Vitromentioning
confidence: 99%
“…USP11 (Ubiquitin carboxyl-terminal hydrolase or ubiquitin specific protease 11) belongs to the ubiquitin specific protease (USP or UBP) family of DUBs. USP11 participates in processes such as TGFβ signaling, pro-inflammatory signaling, viral replication and NF-κB signaling by regulating the protein stability of various targets such as ARID1A, TβRII, CDKN2A, RAE1, XIAP, HPV16-E7 and IκBα (Luo et al, 2020, Deng et al, 2018, Jacko et al, 2016, Lin et al, 2008, Sun et al, 2010, Stockum et al, 2018. USP11 also functions in DSB repair, wherein USP11 deubiquitinates H2AX to regulate the recruitment of RAD51 and 53BP1 to damage foci (Ting et al, 2019, Yu et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin‐specific protease 11 (USP11) is a member of the USP subfamily of DUBs, which has been implicated in the regulation of various cellular functions by controlling its substrates’ stability 7 . Likewise, USP11 malfunction has been found in many types of cancer and related in tumour development and progression 8‐10 . In melanoma, overexpression of USP11 has been frequently observed and is correlated with poor prognosis 11 …”
Section: Introductionmentioning
confidence: 99%